AGRESIVITAS REMAJA DI SEKOLAH MENENGAH ATAS SWASTA KABUPATEN â€œXâ€ (Intuisi : Jurnal Psikologi Ilmiah, 2018)
Abstrak. Siswa di SMA swasta Kabupaten Demak menunjukkan adanya perilaku agresifmeskipun sekolah-sekolah tersebut telah melakukan upaya untukmenghindarkan siswanya dari perilaku agresif. Ini berarti siswa pada SMAswasta masih memiliki emosi yang kurang stabil dan cenderungmemperlihatkan adanya perilaku agresif. Tujuan penelitian ini adalah untukmengetahui gambaran agresivitas remaja di Sekolah Menengah Atas SwastaKabupaten Demak. Jenis penelitian ini yaitu deskriptif kuantitatif. Populasidalam penelitian ini adalah seluruh siswa SMA Swasta Kabupaten Demak.Teknik sampel yang digunakan adalah cluster random sampling sehinggajumlah sampel yang diambil sebanyak 305 siswa yang berasal dari 9 SMASwasta di Demak. Metode pengumpulan data menggunakan skala agresivitasremaja diadaptasi dari Buss-Perry Aggression Questionnaire Scale (BPAQ).skala agresivitas remaja terdapat 29 aitem dengan 26 aitem yang valid dan 3aitem yang gugur. Reliabilitas skala agresivitas remaja dengan koefisien sebesar0,890. Analisis data menggunakan teknsik statistik deskriptif. Hasil penelitianini menunjukkan bahwa (1) Agresivitas remaja pada siswa SMA Swasta diDemak secara umum tergolong dalam kategori sedang cenderung ke rendah. (2)Agresivitas remaja pada siswa SMA Swasta di Demak berdasarkan empat aspekpembentuk yaitu physical agression dalam kategori rendah cenderung ke sedangsedangkan aspek verbal agression, anger dan hostility berada dalam kategorisedang cenderung ke rendah. Aspek yang tertinggi dari siswa sebagai bentukagresivitas adalah hostility sedangkan aspek terendah yaitu physical agression.(3) Agresivitas remaja berdasarkan asal sekolah yang memiliki tingkatagresivitas tertinggi adalah SMA Pembangunan Demak dengan kategori sedangdan agresivitas terendah adalah SMA Abdi Negara dengan kategori rendahcenderung ke sedang. Abstract. Students at Demak Public Private High School demonstrate aggressivebehavior even though the schools have made efforts to prevent their studentsfrom aggressive behavior. This means that students in private high school stillhave less stable emotions and tend to show aggressive behavior. The purposeof this study was to find out the description of aggressiveness of adolescents atPrivate High School Demak District. This research type is descriptivequantitative. The population in this study is all high school students PrivateDemak District. The sample technique used is cluster random sampling so thatthe number of samples taken as many as 305 students from 9 private high80schools in Demak. The data collection method using adolescentaggressiveness scale was adapted from Buss-Perry Aggression QuestionnaireScale (BPAQ). Questionnaire aggressiveness scale adolescents there are 29items with 26 valid items and 3 items that fall. Reliability scale aggressivenessadolescents with coefficient of 0.890. Data analysis using descriptivestatistical technique. The results of this study indicate that (1) aggressivenessof adolescents in private high school students in Demak generally fall into lowto moderate category. (2) The aggressiveness of adolescents in private highschool students in Demak is based on four aspects of physical agression in thelow category tend to moderate while the aspect of agression, anger andhostility are in the moderate to low category. The highest aspect of the studentas a form of aggressiveness is hostility while the lowest aspect is physicalagression. Aggressiveness of adolescents based on the origin of schools thathave the highest aggressiveness level is the High School of DemakDevelopment with the medium category and the lowest aggressiveness is thelow to medium moderate high school Abdi Negara. The advice given is thatschools need to provide direction and guidance periodically so that studentscan reduce aggressive behavior. directives through training and guidance inaddition to BK teachers, guidance also needs dilakukkan by parents ofstudents. For the aspect of hostility as the highest aspect of aggressiveness,students need to actively follow religious activities or discussions such asspiritual extracurricular and discussions of Islamic studies in order to formpositive thoughts. The next researcher also needs to add another variable thatis predicted to affect aggression in adolescents.